(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
In this article, the relevance and theoretical foundations of the problem of developing the professional culture of teachers, the process of developing the professional culture of school teachers, self-control, selfesteem, reflective and creative thinking, value-epistemological and activity-creative analysis. the content of structures and components is highlighted. The article also shows the psychological and pedagogical features and components of the development of the professional culture of teachers.